Implementing the MEA Learning Model to Foster Meaningful Learning: An Evaluation of Its Effectiveness on Student Achievement - Ulfah Hidayati; Fahrian Akbar Hidayah; Kharisma Kharisma; Gusti Ayu Nur Muthmainah; Fikri Aziz; Nurul Azizah; Riyan Terna Kuswanto (PT. Pusmedia Group Indonesia, 2025)
This study was conducted because many students still face difficulties in learning, as the instructional methods used have not yet been implemented in ways that facilitate student understanding. Therefore, the Means-Ends Analysis (MEA) learning model was employed to guide students through a step-by-step thinking process, aiming to make it easier for them to achieve their learning goals and improve their academic performance. The purpose of this study was to examine the effect of the Means-Ends Analysis (MEA) learning model on students' learning outcomes in Islamic Religious Education (PAI) at SMA Negeri 10 Bandar Lampung. The research employed a quantitative method with a quasi-experimental design. The sample was selected randomly, with class X.5 assigned as the experimental group and class X.1 as the control group, each consisting of 30 students. The instrument used was a multiple-choice test. The data analysis began with tests for normality and homogeneity, followed by hypothesis testing using the Independent Samples T-Test if the data were normally distributed and homogeneous, or the Mann-Whitney U Test if the data were not normally distributed, to determine the effectiveness of the MEA learning model on student learning outcomes. The normality test results indicated that the data were not normally distributed (sig. 0.000 < 0.05), so the Mann-Whitney U Test was used, yielding a value of 347.500. The homogeneity test showed that the data were homogeneous (sig. 0.309 > 0.05). The hypothesis test results revealed a significance value of 0.757 (> 0.05), indicating that there was no significant difference between the experimental and control groups. Therefore, the MEA model has not been proven effective in improving learning outcomes in Islamic Religious Education. Other contributing factors, such as student motivation and the teacher’s instructional approach, also need to be considered. The research findings suggest that the implementation of the Means-Ends Analysis (MEA) learning model did not significantly influence the improvement of students’ academic performance. This may be due to several factors, including students’ limited understanding of the steps involved in the MEA model, restricted instructional time, or suboptimal implementation by the teacher. It is suspected that the application was either not optimal or not well aligned with students’ characteristics. Therefore, it is recommended that teachers adopt instructional models that are better suited to students' needs and engage in evaluation and training efforts to enhance the quality of instruction.